Pengaruh Pemberian Ekstrak Etanol Herba Krokot (Portulaca oleracea L.) Terhadap Penurunan Tekanan Sistolik Diastolik Pada Tikus Putih (Rattus norvegicus) Model Hipertensi - Putra, Bayu; Azizah, Rizqi Nur; Kosman, Rachmat; Iskandar , A. Nasyrah (Universitas Borneo Lestari, 2025)
Hypertension is a major risk factor for cardiovascular diseases and can lead to serious complications if not managed optimally. This study aims to evaluate the effects and optimal dose of ethanol extract of purslane herb (Portulaca oleracea L.) in reducing systolic and diastolic blood pressure in hypertensive male rats. The rats were divided into several groups: a negative control, a positive control (captopril), and three treatment groups receiving ethanol extract of purslane at doses of 100, 200, and 300 mg/kg body weight. Systolic and diastolic blood pressure were measured throughout the study to assess the antihypertensive activity of the extract. The results showed that purslane extract at doses of 100, 200, and 300 mg/kg body weight significantly lowered blood pressure, likely due to bioactive compounds such as flavonoids, saponins, and phenols. These compounds exhibit vasodilatory activity, ACE enzyme inhibition, and diuretic effects that contribute to blood pressure reduction in the hypertensive rat model. Ethanol extract of purslane herb (Portulaca oleracea L.) was found to have a significant effect in reducing systolic and diastolic blood pressure in hypertensive rats, with the optimal dose for significant blood pressure reduction being 300 mg/kg body weight